Influence of minimally invasive total hip replacement on hip reaction forces and their orientations. Issue 12 (13th August 2014) - Weber, Tim; Al‐Munajjed, Amir A.; Verkerke, Gijsbertus J.; Dendorfer, Sebastian; Renkawitz, Tobias
ABSTRACT Minimally invasive surgery (MIS) is becoming increasingly popular. Supporters claim that the main advantages of MIS total hip replacement (THR) are less pain and a faster rehabilitation and recovery. Critics claim that safety and efficacy of MIS are yet to be determined. We focused on a biomechanical comparison between surgical standard and MIS approaches for THR during the early recovery of patients. A validated, parameterized musculoskeletal model was set to perform a squat of a 50th percentile healthy European male. A bilateral motion was chosen to investigate effects on the contralateral side. Surgical approaches were simulated by excluding the incised muscles from the computations. Resulting hip reaction forces and their symmetry and orientation were analyzed. MIS THR seemed less influential on the symmetry index of hip reaction forces between the operated and nonoperated leg when compared to the standard lateral approach. Hip reaction forces at peak loads of the standard transgluteal approach were 24% higher on the contralateral side when compared to MIS approaches. Our results suggest that MIS THR contributes to a greater symmetry of hip reaction forces in absolute value as well as force‐orientation following THR. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1680–1687, 2014.